Enhancing the Six Sigma problem-solving methodology using the systems thinking methodologies. (15th May 2009) - Douglas, Alex; Middleton, Saundra; Antony, Jiju; Coleman, Shirley
This theoretical paper describes the two main approaches to problem-solving – the reductionist approach and the systemic approach. The reductionist approach, the dominant problem-solving approach, works well for simple, well-defined 'hard' problems but fails to perform well on complex, ill-defined 'soft' problems and when the parts of a more complex problem are all independently optimised. The holistic approach aims to understand problems holistically and addresses many of the weaknesses of the reductionist approach. This paper identifies evidence to categorise Six Sigma as a reductionist approach to problem-solving. Six Sigma therefore must be open to improvement opportunities particularly if they can address the weaknesses inherent in the reductionist approach. This requires a more holistic approach such as that offered by various systems methodologies. Based on the suggestion of Goh and Xie (2004) that the incorporation of Systems Thinking into Six Sigma could greatly benefit the handling of more complex and dynamic situations, this paper utilises the extant literature to evaluate these to determine if they could broaden the DMAIC approach making it more effective and applicable to both simple and complex problem situations.